DIAGNOSIS OF CANINE PARVOVIRUS INFECTION IN DOGS USING FASTEST PARVOSTRIP AND HAEMAGGLUTINATION TEST - Bodkhe, A M; Bijwal, D L; Kale, K V; Ingle, V C; Jadhav, M B; Khan , L A; Khan , K M (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
In the present study dogs having complaints of anorexia, vomition and foul smelling haemorrhagic diarrhoea were screened for canine parvovirus by subjecting the faecal sample for HA test followed by fastest parvo strip containing monoclonal antibody. Out of 30 dogs 18 were found to be positive for canine parvovirus infection.
Keywords: HA test; Fastest Parvostrip; Canine parvovirus